Development and Validation of Chemometric Assisted RP-HPLC Method for Simultaneous Estimation of Perindopril Erbumine, Indapamide, and Amlodipine Besylate in Bulk and Pharmaceutical Formulation: Pharmaceutical Science-Pharmaceutical Analysis - Sudha, Thomas; Nallasivan, Palani Kumar; Vijayakumar Saranya, Munnusamy; Sarveswaran, Arumugam (International Journal of Life Science and Pharma Research, 2023)
This research paper illustrates a latterly developed, optimized and validated gradient RP-HPLC approach for simultaneous analysis ofIndapamide, Perindopril erbumine and Amlodipine besylate in bulk and pharmaceutical formulation with the assistance of quality by design. Qualityis predicated on desired and predetermined specifications. Understanding various factors, dependent variables, and their interconnection effectsby a desired set of experiments on the responses to be analyzed is an important component of QbD. Several operating conditions of variousprocesses optimization, chromatographic separation performance improvement, and high extraction efficiency were attained by using QbD. Thepowerful chromatographic conditions were done using the HypersilC18 column (250mm × 4.6mm, 5μm particle Size). The UV detector wasadjusted to 215nm. Design of experiments (DoE) was applied for multivariate optimization of the experimental conditions of the RP-HPLCmethod. Three independent factors, mobile phase composition, phosphate buffer strength, and flow rate, were used to design mathematicalmodels. Central composite design (CCD) was used to examine the response surface methodology and fully examine the results of theseindependent factors. The desirability function was used to optimize the retention time and resolution of the analytes simultaneously. Theimproved and anticipated data from the contour diagram consisted of methanol and phosphate buffer (pH 2.5, strength 0.05M) in the ratio of65:35, respectively, at a flow rate of 1.1 ml/min. Using these optimum conditions, baseline separation of both drugs with good resolution and runtime of less than 5.0 min was achieved. The novelty of the developed method was time-consuming, cost-effective, and sensitive. The optimizedassay conditions were validated according to ICH guidelines. Under the optimized state, the linearity ranges were found to be 10-40 μg/mL, 32–128 μg/mL, and 40-160 μg/mL for Indapamide, Perindopril erbumine, and amlodipine besylate, respectively, with correlation coefficients (R2) of0.999. The mean accuracy studied ranged from 99.18 to 99.58%. The percentage coefficient variation value for the precision study was lower than1%. The proposed method showed good precision and repeatability. Hence the developed RP-HPLC method using quality by design can be usedas a routine quality control analysis of indapamide, perindopril erbumine, and amlodipine besylate.